Peran Pola Asuh terhadap Kemandirian Urutan Anak Tengah di Keluarga pada Dewasa Awal - Ramadhani, Layda Rizkina; Idulfilastri, Rita Markus (Lembaga Yasin AlSys, 2025)
This study examines the role of parenting styles in shaping the autonomy of individuals who occupy the middle-child position in the family during early adulthood. The problem arises from the phenomenon that some middle children tend to exhibit lower levels of independence due to feelings of being overlooked within family dynamics, which affects their decision-making abilities, emotional regulation, and personal autonomy. The study aims to determine the extent to which authoritative, authoritarian, permissive, and neglectful parenting styles contribute to the development of autonomy among middle children in early adulthood. Using a correlational quantitative survey method, the research involved 459 participants aged 18–29 years who occupy the middle-child position, with measurements conducted using validated autonomy and parenting style scales. Data were analyzed using Spearman correlation and regression to examine the relationships and the magnitude of parenting style contributions to autonomy. The findings show a significant effect of parenting styles on autonomy (R² = 0.086), indicating that 8.6% of the variance in autonomy is explained by parenting styles. Specifically, the authoritative parenting style provides the largest contribution (R² = 0.031), followed by authoritarian (R² = 0.020) and permissive (R² = 0.010) styles, whereas the neglectful parenting style does not show a significant effect (p = 0.901). These findings underscore that positive parenting, particularly the authoritative style that integrates warmth and control, plays an important role in fostering the autonomy of middle children in early adulthood. The implications highlight the urgency of implementing balanced and supportive parenting practices to optimize the development of middle children’s independence within complex family dynamics.